PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEBIJAKAN DEVIDEN DAN NILAI PERUSAHAAN - Misrah Misrah (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2023)
This study aims to develop and analyze the effect of ownership structure on dividend policy and firm value on manufacturing companies listed on Indonesian stock exchanges. The result showed that managerial ownership variable to dividend policy had positive and significant effect of 3,005 with t value 0,617 with standard of error 4,874 at significance level 0,537 and company value equal to 0,048 with value t equal to 1,079 with standard of error (SE) 0.045 at significance level of 0.281. The institutional ownership of the dividend policy had negative effect of -1.497 with the value of t equal to -2.981 with the standard of error 0,502 at significance level 0,003 and at company value equal to 0,064 with t value equal to 2,990 with standard of error 0,21 at significance level 0.003. While dividend policy to firm value have positive and significant effect equal to 0,025 with t value equal to 37,398 with standard of error 0,001 at 0.000 significance level. The results of this study indicate that when the proportion of managerial and institutional ownership increases, it will be followed by a decrease in dividend payments but will increase the value of the company.